ACL reconstruction using a bone patellar tendon bone (BPTB) allograft or a hamstring tendon autograft (GST): a single-center comparative study - Biz, Carlo; Cigolotti, Augusto; Zonta, Filippo; Belluzzi, Elisa; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: There is still debate on which graft is better indicated for anterior cruciate ligament (ACL) surgical reconstruction. The objective of this study was to evaluate the medium-term clinical outcomes of ACL reconstruction comparing patients managed with bone patellar tendon bone allograft (BPTB) versus patients treated with hamstring autograft (GST). Methods: Patients enrolled during the period 2013-2016 underwent a personal interview with the use of specific evaluation questionnaires (Tegner e Lyshom, Knee Injury and Osteoarthritis Outcome Score, International Knee Documentation Committee), a clinical evaluation with the use of objective functional tests (Lachman test, pivot-shift) and a physical examination of the knee. Results: In this study 43 patients were enrolled: 21 patients were treated by autograft and 22 patients by allograft. Patients who received allograft ACL reconstruction returned to normal sport activity earlier than patients operated on using autograft (11.7±10.3 vs 17.9±14.6 weeks, p